Novel AC magnetic suspension using magnetic resonant coupling - Takeshi MIZUNO (The Japan Society of Mechanical Engineers, 2016)
A novel alternate-current (AC) magnetic suspension using magnetic resonant coupling is proposed and studied both theoretically and experimentally. An AC magnetic suspension with energy transfer function has been developed to achieve magnetic suspension and energy transfer to the suspended object simultaneously. However, the energy transfer efficiency was low in the developed system mainly because there existed a rather wide gap between the primary and secondary circuits. In contrast, the energy transfer technique using magnetic resonant coupling has high efficiency even if there is a wide gap. In this work, this technique is combined with AC magnetic suspension. The fundamental characteristics of the proposed system are studied for a basic model. It is shown analytically that the coupled circuits has two resonant frequencies and attractive force is generated at the lower resonant frequency while repulsive force is generated at the higher resonant frequency. In addition, the self-stabilizing characteristic, which is proper in the tuned LCR circuit levitation, is achievable in the proposed suspension system. A see-saw type experimental apparatus was fabricated for basic experimental study. The theoretical predictions were confirmed experimentally. The self-stabilization was achieved in the fabricated apparatus. It was also shown experimentally that the stiffness and damping characteristics depend on the gap, the amplitude and frequency of the AC voltage source.